1998
DOI: 10.1007/s004670050541
|View full text |Cite
|
Sign up to set email alerts
|

IgG subclass/IgM ratio and response to therapy in focal segmental glomerulosclerosis

Abstract: Focal segmental glomerulosclerosis (FSGS) is relatively steroid resistant and no clinical or histological marker can predict the response to therapy. To investigate the role of serum immunoglobulin subclass/IgM in predicting the response to therapy in FSGS, serum concentrations of total IgG, IgG subclasses, and the ratio of serum IgG subclasses to total IgG (% IgG subclass) were measured in 27 children during the acute nephrotic state. Prednisolone, cyclophosphamide, and Persantine (dipyridamole) were given fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…These results agree with some other studies,[2324] who suggested a better response to treatment for patients with idiopathic NS (including SSNS and FSGS with a high serum IgG-1/IgM ratio and one concluded that IgG/IgM ratio was found to be significantly lower in the NS patients than in the healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with some other studies,[2324] who suggested a better response to treatment for patients with idiopathic NS (including SSNS and FSGS with a high serum IgG-1/IgM ratio and one concluded that IgG/IgM ratio was found to be significantly lower in the NS patients than in the healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…Also Warshaw et al confirmed low IgG-1 and 2 in relapse compared to remission [11] but did not compare the latter group to healthy controls. Two recent studies suggested a better response to treatment for patients with idiopathic nephrotic syndrome (including SSNS and focal segmental glomerulosclerosis (FSGS) with a high IgG-1/IgM ratio, but did not give comparative details for IgG subclasses among study groups or controls [16,17]. Also, determinations of IgGS in nephrotic syndrome have been included in studies of charge selectivity of the glomerular basement membrane (GBM), but again did not give details on serum levels in this disorder [18].…”
Section: Discussionmentioning
confidence: 99%